Valuing Derivatives in Commercial Banks of Emerging Markets - Application to Slovenian Market - Grum, Andraž (Ekonomika, 2005)
In emerging market economies there is usually no institutionalised derivative market. Like in every other market-oriented economy, there exists the need for such instruments, especially in the corporate and financial sectors. In practice, the main market or position risk that a corporate sector is exposed to is the exchange rate or currency risk. The shortage of standardized derivatives is partly covered by unstandardized, tailormade derivatives issued by commercial banks to satisfy the specific needs of clients. Not surprisingly, a large portion of unstandardized derivatives issued by commercial banks comes in the type of forward agreements and I or options, with a foreign currency as the underlying asset. Because those derivatives are “tailormade”, they often have characteristics for which they can be classified as exotic derivatives. To manage efficiently the market risk, the issuer of such derivatives has to address the issue of valuation of those instruments. In practice, the most effective method of valuation of exotic derivatives has been found to be the Monte Carlo simulation based on the parametric model of the underlying asset price dynamics. Using the Monte Carlo simulation for pricing options raises several issues such as measuring the accuracy of simulated prices and determining the number of simulations required for the desired level of accuracy.